1999
DOI: 10.1002/(sici)1520-6866(1999)19:2<87::aid-tcm2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of male-mediated F1 effects in mice treated acutely and sub-chronically with urethane

Abstract: In order to investigate the alleged potential of paternally administered urethane to cause foetal abnormalities and heritable tumours, male CD‐1 mice were treated with urethane, either acutely by intraperitoneal injection at doses of 1.25 and 1.75 g/kg bodyweight (bwt) or sub‐chronically in the drinking water at 1.25 for 10 weeks and 3.75 mg/ml for 9 weeks or vehicle for the control groups. They were mated to untreated females 1 week later. Uterine contents of half the pregnant females were examined just befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…48 However, for urethane, there were negative results for dominant lethality and congenital malformations after subchronic exposure in the drinking water, although an increase in tumors in males was observed after acute intraperitoneal treatment. 49 A Japanese study in ICR mice after acute intraperitoneal treatment also reported negative results for dominant lethal mutations, confirming results by other workers, but demonstrated an increase in congenital malformations, tumors in the F1 generation and transmitted tumors in the F2 and F3 generations. 50 It is assumed that such effects outlined above have been produced as a result of alterations induced in the male germ cells because of their heritability through the generations.…”
Section: Paternal Exposure To Chemicalssupporting
confidence: 82%
See 4 more Smart Citations
“…48 However, for urethane, there were negative results for dominant lethality and congenital malformations after subchronic exposure in the drinking water, although an increase in tumors in males was observed after acute intraperitoneal treatment. 49 A Japanese study in ICR mice after acute intraperitoneal treatment also reported negative results for dominant lethal mutations, confirming results by other workers, but demonstrated an increase in congenital malformations, tumors in the F1 generation and transmitted tumors in the F2 and F3 generations. 50 It is assumed that such effects outlined above have been produced as a result of alterations induced in the male germ cells because of their heritability through the generations.…”
Section: Paternal Exposure To Chemicalssupporting
confidence: 82%
“…By using this type of study design, we have examined the following compounds using chronic and acute exposure: cyclophosphamide, 1,3-butadiene and urethane (ethyl carbamate) ( Table 1). [42][43][44][45][46][47][48][49] Cyclophosphamide was positive for all endpoints in the rat after chronic gavage exposure. 43,44 This effect has also been shown by others 45 and led to the belief that chronic exposure might be a more realistic model than acute exposure, as man is chronically exposed in the workplace and environmentally.…”
Section: Paternal Exposure To Chemicalsmentioning
confidence: 90%
See 3 more Smart Citations